Heat count. (Economist, 2009)
The article focuses on so-called "carbon-management software," computer software designed to monitor energy use and greenhouse gas emission by corporations. Use of such software is increased as companies seek both to cut costs of energy use and comply with government regulations on carbon emissions. The companies SAP and Oracle are forecast to dominate the market for this software.